The Influence of Musical Instrument Quality, Interior Design, Service Quality, and Location on Leasing Decisions: R.A.P Studio Musik Case Study - Anggara, Reska; Sigit Handoko (UPY Business and Management Journal (UMBJ), 2025)
Purpose: This study aims to analyze the influence of the quality of musical instruments, interior design, service quality, and location on consumers' decisions to rent at R.A.P. Music Studios. Methodology: This research is quantitative, using questionnaires as a research instrument. Samples were taken by the non-probability accidental sampling method. Data analysis for validity test using Pearson product moment test, Reliability test using Alpha Cronbach's, Normality test using Kolmogorov-Smirnov, Multicollinearity test using regression by looking at tolerance value, Heteroskedasticity test using Glejser test, Linearity test using linear regression test, T test is used to see the differences between variables and F test is used to see the contribution of the influence of independent variables on dependent variables. All data testing uses the SPSS application version 24.0. Findings: The findings in this study are that the quality of musical instruments, interior design, service quality, and location have a positive effect both jointly and between indicators on consumers' decision to use rental at R.A.P music studios. Originality: This study focuses on supporting factors such as the quality of musical instruments, interior design, service quality, and location on rental decisions at the R.A.P music studio. Research limitations: This study has not included intervening variables that influence the independent variables on rental decisions at R.A.P. Music Studio. Practical implications: Companies engaged in music studio rentals can consider the variables in this study to be used as evaluation material and improve company performance.